Segmentation of cells in digital images of the corneal endothelium. - Toledo Crow, Ricardo (Revista Mexicana de Ingenieria Biomedica, 1991)
A method is proposed to segment images obtained from a corneal endothelium specular microscope. Because they are taken "in vivo", they are extremely noisy and therefore cannot be segmented by classical methods. The proposed method uses the generation of binary images from the original and the extraction of the contours of the cells is carried out with connectivity operations such as dilation and skeletonization.